Better Ways of Sharing - Clark, Dave (Critical Studies in Improvisation / Études critiques en improvisation, 2021)
Dave Clark is an improvising drummer and founder of the Toronto-based Woodchoppers improv collective. In this piece, he stresses the need for more equitable methods of sharing the revenue generated by musicians working in the creative commons, and discusses an open letter that he wrote to SOCAN in May 2020.